2020
DOI: 10.1088/1361-6463/abb727
|View full text |Cite
|
Sign up to set email alerts
|

Defect incorporation in In-containing layers and quantum wells: experimental analysis via deep level profiling and optical spectroscopy

Abstract: Recent studies demonstrated that the performance of InGaN/GaN quantum well (QW) light emitting diodes (LEDs) can be significantly improved through the insertion of an InGaN underlayer (UL). The current working hypothesis is that the presence of the UL reduces the density of non-radiative recombination centers (NRCs) in the QW itself: during the growth of the UL, surface defects are effectively buried in the UL, without propagating towards the QW region. Despite the importance of this hypothesis, the concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 30 publications
(46 reference statements)
6
27
0
Order By: Relevance
“…The strong impact of type-I PDs on CL intensity and IQE indicates they possess energy levels near the middle of the InGaN bandgap, since such midgap states are known to be efficient non-radiative recombination centres. 2,39 Our CL-derived type-I PD densities are in good agreement with previous results from macroscale measurements by Piva et al 37 (Fig. 4), which corroborates that we are spatially resolving individual PDs.…”
Section: Resultssupporting
confidence: 91%
“…The strong impact of type-I PDs on CL intensity and IQE indicates they possess energy levels near the middle of the InGaN bandgap, since such midgap states are known to be efficient non-radiative recombination centres. 2,39 Our CL-derived type-I PD densities are in good agreement with previous results from macroscale measurements by Piva et al 37 (Fig. 4), which corroborates that we are spatially resolving individual PDs.…”
Section: Resultssupporting
confidence: 91%
“…An example of the implementation of this technique was provided by Piva et al, [ 49 ] where the authors studied the efficacy of the insertion of a superlattice underlayer (SL UL), aimed at blocking the growth of defects toward the active region in an InGaN‐based LED. As shown in Figure , the authors evaluated traps concentration N normalT with the formula reported above and found a higher quantity of defects within the active region of the sample without the UL.…”
Section: Experimental Techniques For Defects Analysismentioning
confidence: 99%
“…In fact, it was not possible to achieve the same results by replacing InGaN with GaN grown at lower temperature, and thus with low defects concentration, which indicates that the presence of indium atoms has a determining impact on defect generation. [ 19,49,75 ]…”
Section: Defects In Gan Ledsmentioning
confidence: 99%
See 2 more Smart Citations